Cassava germplasm strategies for Africa - Allem, A.C.; Hahn, S.K. (1991)
The types of germplasm needed for the different agroecological zones where cassava is grown are outlined briefly in terms of what the main supplier (South America) has to offer. Africa's Atlantic coastal belt, its tropical rain forests, its extensive savannas, and the arid zones are examined in relation to similar zones in South America, with particular emphasis on Brazil, which alone can meet most African needs thanks to the diversity of its edaphoclimatic environments. The topic of genetic erosion is also addressed; there is no tangible evidence, however, that cassava is undergoing serious genetic erosion in its centers of origin (American neotropics). Major cassava germplasm collections are listed for the Americas, Africa, and Asia. Genetic resources of wild Manihot species are also reviewed. Future strategies should consider more temperate latitudes farther south, salinity, atmospheric humidity, and reproductive biology. High priority should be given to collecting germplasm for transfer to African regions, as follows: coastal cv., riverine cv., cv. with yellow flesh, drought-tolerant cv., and wild populations of cassava in the neotropics. (CIAT).